Development of A Collaborative Web-Based Academic Supervision Model to Improve Learning Quality - Fransiskus Junirianto; Yari Dwikurnaningsih; Herry Sanoto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
The background of this study is based on the challenges faced by school principals in conducting conventional academic supervision, which is often hindered by time constraints, limited resources, and data accessibility issues. To address these problems, a web-based academic supervision system was developed. This study employs the Research and Development (R&D) method with a 4D model approach (Define, Design, Develop, Disseminate). In the Define stage, problem identification was carried out through observations and interviews at Sidorejo Kidul 2 Public Elementary School. The analysis results indicated that academic supervision had been conducted manually and was not systematically documented. In the Design stage, a prototype of the web-based academic supervision system was designed with key features such as supervision data management, supervision report generation, and real-time feedback. In the Develop stage, validation was conducted by information technology and academic supervision experts, revealing that the web-based supervision system falls into the "Highly Feasible" category, with a feasibility percentage of 83.33% for the technology aspect and 92.9% for the academic supervision aspect. A field trial involving school principals, teachers, and educational staff showed that the system achieved a user satisfaction rate of 81.4%.